A metabolic stability determination of Tetrahydrothiazolopyridine derivative a selective 11β-hydroxy steroid dehydrogenase type 1 (11β-hsd1) inhibitor - MURUGESH KANDASAMY; MUHAMMED SALIHIN; MALLIKARJUNA RAO PICHIKA; SLAVKO KOMARNYTSKY; THIRUMURUGAN RATHINASABAPATHY (International Journal of Pharma and Bio Sciences, 2017)
A potent tetrahydrothiazolopyridine derivative TR-018A that acts as an inhibitor of 11β-Hydroxysteroid dehydrogenase isoform 1 was investigated for its metabolic stability in mouse, rat and human liver microsome. The study were carried out in two parts, one is to develop a method in high-performance liquid chromatography for TR-018A and the other is to investigate its metabolic stability in rat, human and mouse liver microsome. The chromatograms and retention time for TR-018A were analyzed at different time points; control, 0, 5, 15, 30 and 60 minutes by using Betasil C18 column (5 µm particle size, 150mm X 4.6mm by Thermo Scientific.) at column temperature 40°C with an isocratic mobile phase containing acetonitrile and 0.2% formic acid of 0.7mL/min flow with 15 minutes run time. TR-018A chromatograms were detected and recorded at λ = 283nm with the injection volume of 20µL. Under the provided experimental conditions, it was observed that Tetrahydrothiazolopyridine compound TR-018A was stable in mouse, rat and human liver microsomes and stable up to 80% at 30 min of incubation. This study shows that the compound is a metabolically stable and the results indicated that 11β-HSD1 inhibition by TR-018A may serve as a potential novel treatment for Type 2 diabetes and worth conducting further preclinical evaluations.